Brain magnetic resonance imaging in imported malaria - Andreas M. Frölich; Pinkus Tober-Lau; Michael Schönfeld; Thomas T. Brehm; Florian Kurth; Christof D. Vinnemeier; Marylyn M. Addo; Jens Fiehler; Thierry Rolling (Malaria Journal, 2019)
Abstract Background Previous studies have documented a spectrum of brain magnetic resonance imaging (MRI) abnormalities in patients with cerebral malaria, but little is known about the prevalence of such abnormalities in patients with non-cerebral malaria. The aim of this study was to assess the frequency of brain MRI findings in returning travellers with non-cerebral malaria. Methods A total of 17 inpatients with microscopically confirmed Plasmodium falciparum non-cerebral malaria underwent structural brain MRI at 3.0 Tesla, including susceptibility-weighted imaging (SWI). Presence of imaging findings was recorded and correlated with clinical findings and parasitaemia. Results Structural brain abnormalities included a hyperintense lesion of the splenium on T2-weighted imaging (n = 3) accompanied by visible diffusion restriction (n = 2). Isolated brain microhaemorrhage was detected in 3 patients. T2-hyperintense signal abnormalities of the white matter ranged from absent to diffuse (n = 10 had 0–5 lesions, n = 5 had 5–20 lesions and 2 patients had more than 50 lesions). Imaging findings were not associated with parasitaemia or HRP2 levels. Conclusion Brain MRI reveals a considerable frequency of T2-hyperintense splenial lesions in returning travellers with non-cerebral malaria, which appears to be independent of parasitaemia.